Rancang Bangun STIKI Class Facilities E-Complaint - Ariasih, Ni Kadek; Gede Sri Artha, I Made (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 8, No. 2 Agustus 2017, 2017)
STMIK STIKOM Indonesia is one of the institutions in the field of computer-based education. In order t o support the effectiveness of the implementation of teaching and learning activities that take place , it is need a service that support the availability of adequate class facilities and complaints services if there are constraints on facilities in the classroom. So far, the management of complaints complaints against classroom facilities or in the labarotorium which is handled by the Household Management Section is still on manua basis . In terms of record and handle complaints it is required information system which called STIKI Class Facilities E-Complaint. This system can assist the Household Management Section in monitoring complaints from the condition of existing room facilities if experiencing problems and also can improve the quality of service in handling complaints. The software development process model used is prototype and Web-based model with PHP and MySQL database.
Keywords: pelayanan,keluhan,fasilitas kelas